Health Care Utilization and Health Care Expenditure of Nepali Older Adults - Acharya, Sabnam; Ghimire, Saruna; Jeffers, Eva M.; Shrestha, Naveen (Frontiers in Public Health, 2019)
Aging is associated with multiple chronic conditions. In older age, health needs and demand for health services utilization increase. There are limited data in Nepal on health care utilization as well as health care costs among the elderly population. Therefore, it is imperative to explore the factors hindering access to health care among Nepalese older adults. Our study aims to explore the health care utilization and expenditure among Nepali older adults. Method: A community-based cross-sectional survey was conducted among 401 older adults residing in Pokhara Lekhnath metropolitan of Nepal. The survey tool was adapted from the Study on Global Ageing and Adult Health (SAGE)’s questions on “Health Care Utilization”. The predictors of health care utilization were assessed in binary logistic regression models. Results: Study participants, mean (±SD) age 70.2 (±8.0) years, had various preexisting conditions such as hypertension (37.7 %), gastritis (28.4 %), asthma (25.4 %), and arthritis (23.4 %) reported in the past 12 months but only 70% visited a health facility. A notable proportion (30%) of participants didn’t utilize health services despite having a health problem. The utilization of out-patient and in-patient health services were 87.5% and 14.6% respectively. The use of private health facilities (56.4%) was high compared to the use of government health facilities (35.7%). Privileged ethnicity, living with a partner, higher annual income, knowledge of social insurance, and multi-morbidity were associated with higher odds of utilizing health services. Participants of privileged ethnicity, with higher household income, attending private health facility, and having multi-morbidities had significantly higher out of pocket health expenditures. Conclusions: A notable proportion of elderly participants did not utilize health services despite having a health problem. The public health system must develop effective strategies to attract this segment of the society. High dependency on private health facilities, as noted in the study, will only lead towards higher out of pocket health expenditures. The health benefits of regular health screenings must be disseminated among the elderly population. Developing quality and affordable health care services for older adults to ensure equity in accessibility will be a major task for the public health system in Nepal.